Hope in palliative care nursing: concept analysis. (2nd June 2021) - Guedes, Ana; Carvalho, Matilde Silva; Laranjeira, Carlos; Querido, Ana; Charepe, Zaida
Abstract : Background: Hope has long been considered essential to humans in several disciplines, nursing included. At the end-of-life, hope is a complex and dynamic emotion, and there have been different interpretations and conceptions of hope. Aim: To develop hope in palliative care as an evidenced-based nursing concept: analyse its attributes, antecedents and consequences. Method: This study follows Walker and Avant's concept analysis: (a) select a concept; (b) determine the aims or purposes of analysis; (c) identify as many uses of the concept as possible; (d) determine the defining attributes; (e) identify a model case; (f) identify borderline and contrary cases; (g) identify antecedents and consequences; and finally (h) define the empirical referents. Findings: Antecedents included symptom control, existential suffering, interpersonal relationships and the establishment of realistic goals. The synthetic attributes were a positive outcome expectancy and a process oriented towards the present and future. The concept's consequences were quality of life, survival, acceptance and a peaceful death. Conclusion: This study revealed a strong history of publications on the subject. The analysis of attributes, antecedents and consequences of the concept of hope contributed to understanding its relevance to palliative care nursing and provided suggestions for effective interventions and future research.